Preparing for Peace and Prosperity : Steps Ahead for the Arab World - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group discusses measured hope and optimism, to share a vision for a path forward, to a just and sustainable future in the Middle East and North Africa. He talks about a way forward to help not only Syria rebuild, but also to help Lebanon, Jordan, Turkey, and Iraq recover from the massive spillover effects of the war is to be supported by the principles of co-existence, tolerance, compromise, transparency, good governance, and inclusive economic growth. He talks about the need for improvement in quality of education. He talks about development that requiring a commitment to transparency on the part of governments, and well-informed citizens to hold governments accountable. He speaks about helping women overcome the multiple legal and cultural constraints that have kept their labor force participation in the region at 29 percent, the lowest in the world. He talks about the young people here and throughout the Arab world deserve a chance to grow up in a region that is focused on creating jobs, not on conflict—a region focused on inclusive growth, not on growth for just the elite. The region needs to invest in its people with strong education and health systems.